2021
DOI: 10.1192/bjo.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clinical outcomes, service satisfaction and well-being in people using acute day units and crisis resolution teams: cohort study in England

Abstract: Background For people in mental health crisis, acute day units (ADUs) provide daily structured sessions and peer support in non-residential settings, often as an addition or alternative to crisis resolution teams (CRTs). There is little recent evidence about outcomes for those using ADUs, particularly compared with those receiving CRT care alone. Aims We aimed to investigate readmission rates, satisfaction and well-being outcomes for people using ADUs and CRTs. Method W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A review in 2011 found that for some service users, ADUs were a viable alternative to inpatient admission with similar rates of readmission [10]. More recent studies carried out in England found that people supported by ADUs had a positive experience [11] and similar readmission rates to service users of CRTs [12]. Although ADUs can be found across Europe [13], in England they are much less widely implemented than CRTs [14].…”
Section: Introductionmentioning
confidence: 99%
“…A review in 2011 found that for some service users, ADUs were a viable alternative to inpatient admission with similar rates of readmission [10]. More recent studies carried out in England found that people supported by ADUs had a positive experience [11] and similar readmission rates to service users of CRTs [12]. Although ADUs can be found across Europe [13], in England they are much less widely implemented than CRTs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Even taking into account these differences between the groups, there was no significant difference between them in terms of re-admission (HR 0.94, 95% CI 0.67 to 1.32). At 8-12 weeks, after accounting for baseline differences in participant characteristics, ADU participants had significantly higher satisfaction [CSQ score: 26.66 (SD 5.04) vs. 24.37 (SD 6.57)], with better well-being 19.02 (SD 5.03)] and lower depression [CES-D-10 14.4 (SD 6.0) vs. 16.6 (SD 5.7)] than CRT participants. These results indicate that, despite serving a more unwell client group, ADUs produce comparable outcomes in terms of re-admission, and better satisfaction, depression and well-being results than CRTs.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Chapter 6 Work package 2.1: cohort studya comparison of re-admission rates, satisfaction and mental health outcomes in people using acute day units and people using only crisis resolution teams in four localities in England P arts of this chapter have been reproduced from Lamb et al 19 This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/ licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.…”
Section: Adumentioning
confidence: 99%
See 1 more Smart Citation
“…A review in 2011 found that for some service users, ADUs were a viable alternative to inpatient admission with similar rates of readmission (8). More recent studies carried out in England found that people supported by ADUs had a positive experience (9) and similar readmission rates to service users of CRTs (10). Although ADUs can be found across Europe (11), they are much less widely implemented than CRTs in England (12).…”
Section: Introductionmentioning
confidence: 99%